The Dynamics of Social Innovation Research in Entrepreneurship Based on Bibliometric and Co-Word Analysis of Publications from 2012 to 2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
This study aims to examine the development and research dynamics of social innovation within the field of entrepreneurship through a bibliometric and co-word analysis of scientific publications. The data were obtained from the Scopus database covering the period from 2012 to 2024. Bibliometric techniques were applied to identify publication patterns, collaboration networks, and thematic structures within the literature. The analysis was conducted using VOSviewer to visualize co-authorship networks, institutional collaborations, country collaborations, keyword co-occurrences, overlay visualization, and density visualization. The results reveal that social innovation, sustainable development, and entrepreneurship constitute the central themes of the research landscape. The findings also show that sustainability-related topics and social enterprise concepts play a significant role in shaping the direction of scholarly discussions in this field. Furthermore, recent research trends indicate the growing importance of entrepreneurship education, digitalization, artificial intelligence, and innovation ecosystems in advancing social innovation practices. The collaboration network analysis demonstrates that research in this area involves extensive international partnerships, with several countries and institutions acting as major hubs in global knowledge production. The study highlights the interdisciplinary nature and increasing global relevance of social innovation research in entrepreneurship, while also identifying emerging themes that may guide future research and policy development.